2018
DOI: 10.15252/embj.201798732
|View full text |Cite
|
Sign up to set email alerts
|

Error‐free DNA damage tolerance pathway is facilitated by the Irc5 translocase through cohesin

Abstract: DNA damage tolerance (DDT) mechanisms facilitate replication resumption and completion when DNA replication is blocked by bulky DNA lesions. In budding yeast, template switching (TS) via the Rad18/Rad5 pathway is a favored DDT pathway that involves usage of the sister chromatid as a template to bypass DNA lesions in an error-free recombination-like process. Here, we establish that the Snf2 family translocase Irc5 is a novel factor that promotes TS and averts single-stranded DNA persistence during replication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 93 publications
(166 reference statements)
0
19
0
Order By: Relevance
“…However, neither Mec1 and Tel1 kinases nor H2A phosphorylation was required for cohesin binding to HU-arrested replication forks. In fact, only the mec1 Δ tel1 Δ double deletion led to a significant decrease of cohesin levels on chromatin [47,191]. This suggests that molecular requirements for cohesin accumulation at stalled replication forks may differ from the mechanisms determined for DSB-induced cohesin recruitment.…”
Section: Mechanisms Of Cohesin Recruitment To Dna Damage Sitesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, neither Mec1 and Tel1 kinases nor H2A phosphorylation was required for cohesin binding to HU-arrested replication forks. In fact, only the mec1 Δ tel1 Δ double deletion led to a significant decrease of cohesin levels on chromatin [47,191]. This suggests that molecular requirements for cohesin accumulation at stalled replication forks may differ from the mechanisms determined for DSB-induced cohesin recruitment.…”
Section: Mechanisms Of Cohesin Recruitment To Dna Damage Sitesmentioning
confidence: 99%
“…In the absence of IRC5 , the cohesin complexes accumulate more slowly and to a lesser extent at early replication origins during MMS treatment. These data may point to an important role of chromatin structure in replication stress-induced cohesin enrichment at replication sites [191]. It was also shown that in response to HU treatment, Smc1, Smc3, and Scc1 cohesin subunits are ubiquitylated by the Rsp5 Bul2 ubiquitin ligase (NEDD4 in humans) in a Mec1-dependent manner [192].…”
Section: Mechanisms Of Cohesin Recruitment To Dna Damage Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…HELLS implication in genome integrity has also been detected in Neurospora crassa ( Basenko et al, 2016 ) and Saccharomyces cerevisiae ( Litwin et al, 2017 ). In S. cerevisiae , the HELLS orthologue Irc5 is required for DNA damage tolerance, and this function implies the loading of the cohesin complex at replication forks ( Litwin et al, 2018 ). In S. cerevisiae , cohesin recruitment facilitates DSB repair ( Ström et al, 2004 ; Unal et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%